Coordination Behavior of [Cp′′2Zr(η1:1‐P4)] towards Different Lewis Acids. Issue 43 (23rd June 2017) - Seitz, Andreas E.; Vogel, Ulf; Eberl, Miriam; Eckhardt, Maria; Balázs, Gábor; Peresypkina, Eugenia V.; Bodensteiner, Michael; Zabel, Manfred; Scheer, Manfred
Abstract: A detailed method for the preparation of [Cp′′2 Zr(η 1:1 ‐P4 )] (1 ) is presented. The coordination behavior of1 towards Lewis acidic transition metal complexes of tungsten, manganese, and iron, respectively, and main group compounds (AlMe3, AlEt3 ) was investigated in detail by computational and experimental studies. In doing so, a series of unprecedented complexes with different coordination modes and multiple coordination numbers of the tetraphosphabicyclo[1.1.0]butane framework were synthesized. All products, as well as the starting materials, were comprehensively characterized by NMR spectroscopy, mass spectrometry, elemental analysis, and single crystal X‐ray structural analysis. Abstract : Complex coordination : A detailed procedure for the preparation of [Cp′′2 Zr(η 1:1 ‐P4 )] (1 ) is presented and the coordination behavior of this complex towards Lewis acidic transition metal fragments of tungsten, manganese, and iron, respectively, and main group compounds (AlMe3, AlEt3 ) was comprehensively investigated by computational and experimental studies.